2006
DOI: 10.1128/jvi.02427-05
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine Increases Human Immunodeficiency Virus Type 1 Vector Transduction of Primary Mouse Cells

Abstract: Murine primary cells are poorly permissive to human immunodeficiency virus type 1 (HIV-1) vector infection. Retroviral infectivity is influenced by dominant inhibitors such as TRIM5␣. Sensitivity to TRIM5␣ is altered by interactions between cyclophilin A and the HIV-1 capsid. Here we demonstrate that competitive inhibitors of cyclophilins, cyclosporine or the related Debio-025, stimulate HIV-1 vector transduction of primary murine cells, including bone marrow and macrophages, up to 20-fold. Unexpectedly, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…In general, mouse cells do not support HIV-1 replication because of host range barriers at various steps including virus entry, nuclear import [14], RNA splicing [26], polyprotein processing, assembly, and release. For example, Noser et al [13] reported that HIV-1 infection of murine cells is inhibited by dominant factors related to immunophilins and that competitive inhibitors of cyclophilins, including cyclosporin and the related compound Debio-025, stimulated HIV-1 vector transduction of primary murine bone marrow-derived cells and macrophages up to 20-fold. On the basis of these findings we tested the impact of cyclosporin A on mouse MSCs and did not observe improvements in transduction efficiencies (Ricks, unpublished).…”
Section: Optimized Conditions For Mouse Msc Transductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, mouse cells do not support HIV-1 replication because of host range barriers at various steps including virus entry, nuclear import [14], RNA splicing [26], polyprotein processing, assembly, and release. For example, Noser et al [13] reported that HIV-1 infection of murine cells is inhibited by dominant factors related to immunophilins and that competitive inhibitors of cyclophilins, including cyclosporin and the related compound Debio-025, stimulated HIV-1 vector transduction of primary murine bone marrow-derived cells and macrophages up to 20-fold. On the basis of these findings we tested the impact of cyclosporin A on mouse MSCs and did not observe improvements in transduction efficiencies (Ricks, unpublished).…”
Section: Optimized Conditions For Mouse Msc Transductionmentioning
confidence: 97%
“…Furthermore, it was shown that the transduction process and the high levels of reporter gene expression achieved did not have any deleterious effect on the ability of the cells to differentiate down the adipogenic pathway. Efficient lentivirus-mediated gene transfer into mouse MSCs has been more challenging, in part because of host range barriers for HIV-1 in such cells, including tissue-specific restriction factors [13] and blocks in the nuclear uptake of the preintegration complex [14].…”
Section: Introductionmentioning
confidence: 99%
“…To address the influence of IFN-␣ treatment on the TRIM5␣ rh -mediated postentry restriction of HIV-1 infection, we first examined whether IFN-␣ treatment could render FrhK4 cells less permissive to a vesicular stomatitis virus G protein (VSV-G)-pseudotyped HIV-1 vector infection. A green fluorescent protein (GFP)-carrying HIV-1 vector was produced as described previously (28). We pretreated FrhK4 cells with 0, 10, 20, 50, and 100 U/ml of IFN-␣ for 6 h, followed by infection with increasing amounts of HIV-1 vectors.…”
mentioning
confidence: 99%
“…GFP-carrying SIV, N-MLV, and NB-MLV vectors were prepared using FuGENE 6 as described previously (30,32). The vector-containing culture supernatant was collected and filtered through a 0.45-m syringe filter 48 -72 h post-transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Flotillin-1/Reggie-2 primers used were 5Ј-GTTTA-CACTCGCCATGGGGTCCCCATCTCAG-3Ј and 5Ј-GCGGCC-TTCTTCAGTTCGTAATCTCTCTGTGC-3Ј. ␣-Tubulin primer set used in these experiments was described previously (30).…”
Section: Methodsmentioning
confidence: 99%